2018
DOI: 10.1016/j.jcol.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postoperative complications in Crohn disease: analysis of 173 patients

Abstract: Background and objectives  Surgery for Crohn disease has a wide range of factors that are being studied as possible risk factors for postoperative complications. The later are a major problem in those patients and are associated with longer hospital stays and increased mortality and morbidity. Despite the debate regarding the influence of patients’ characteristics, preoperative and operative details, the risk factors are not fully identified. The debate has been focused on the new medical therapy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Finally, 51 cohort studies [ 21 , 22 , 23 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ] fulfilled the inclusion criteria, three [ 21 , 55 , 89 ] of which included at least two discrete data sets and were subjected to qualitative and quantitative analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, 51 cohort studies [ 21 , 22 , 23 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ] fulfilled the inclusion criteria, three [ 21 , 55 , 89 ] of which included at least two discrete data sets and were subjected to qualitative and quantitative analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The systematic review and meta-analysis investigate 47 retrospective [ 21 , 22 , 23 , 46 , 47 , 48 , 50 , 51 , 53 , 54 , 55 , 56 , 57 , 58 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ] and four prospective [ 49 , 52 , 59 , 67 ] studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The specific impact of previous intestinal resection on postoperative complications in patients with CD has not been determined. One study reported that 47.6% of postoperative complications occurred in patients with a history of previous abdominal surgery ( n = 10, P = 0.310), although the difference was not statistically significant[ 20 ]. Other studies have found that previous abdominal surgery is a significant risk factor for postoperative complications[ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%